The Greeks under the Jurisdiction of the Archbishop of Karlovci in the Eighteenth Century - Vasin, Goran; Ninković, Nenad; Radulović, Ifigenija (The Historical Review/La Revue Historique, 2021)
In the territory of the Habsburg Monarchy during the eighteenth century, the only Orthodox Church whose jurisdiction was recognised by the imperial authorities was that of the Archbishopric of Karlovci, which up to 1766 was an autonomous part of the Patriarchate of Peć. The believers who were part of this archbishopric had the freedom to profess their religion, which is why the Greeks who took up temporary residence in the towns of the Habsburg Monarchy turned to its archbishop when seeking their religious rights. However, there was an important difference in the status of the Greeks and the Serbs, since the former would not become subjects of the Habsburg Monarchy on a large scale until the 1760s while the former were already subjects. Due to their shared religion, in smaller settlements where they were a minority the religious needs of the Greeks were met within the existing Serbian parishes. This article describes the development of Greek parishes under the administration of the archbishop of Karlovci, how the authorities treated them and how they attained their religious rights.